THE CORRELATION BETWEEN STUDENTSâ VOCABULARY MASTERY AND THEIR ABILITY IN TRANSLATING ENGLISH SENTENCES INTO BAHASA INDONESIA: A Study at the Third Semester Students of English Department of STKIP PGRI Bandar Lampung in 2013/2014 - Subari, Imam (Lentera: Jurnal Ilmiah Kependidikan, 2013)
As prospective English teachers, the students of English Department of STKIP PGRI Bandar Lampung, have to master the four English language skills; speaking, listening, writing, and reading and English language components such as grammar, vocabulary, etc. Further, they also have to master translating ability as well. By mastering all those language skills and components, they will be able to do their job as English teachers well.This research is aimed at investigating the correlation between studentsâ vocabulary mastery and their ability in translating English sentences into Bahasa Indonesia of the third semester students of English Departement of STKIP-PGRI Bandar Lampung.From the vocabulary test given, it was obtained that the highest score was 90, the lowest score was 55 and the average score was 80. It means that the students have good vocabulary mastery. For the translating test given, the highest score was 95, the lowest score was 60, the average score was 80. It means that they also have good ability in translating English sentences into bahasa Indonesia. Based on the data analysis by using Product Moment formula at the significance level 5%, , the result of research shows that r count = 0.636 is highert than r table=0.312 by n=40. The result showed that the correlation between studentsâ vocabulary mastery and their ability in translating English sentences into bahasa Indonesian was high, and r count=0.636 was highest than 0.00. So it can be concluded that there is positive and significant correlation between the studentsâ vocabulary mastery and their ability in translating English sentences into bahasa Indonesia of the third semester students of English Departemnt of STKIP-PGRI Bandar Lampung. This research finding implies that the better of the studentsâ vocabulary mastery, the better the studentsâ translating ability will be. So that to increase the studentsâ translating ability, we can increase their vocabulary mastery.